Determinants of Firm Innovation in Indonesia: The Role of Institutions and Access to Finance - Mahendra, Edo; Zuhdi, Ubaidillah; Muyanto, Ratnawati (Economics and Finance in Indonesia, 2015)
This paper investigates the determinants of firm innovation in Indonesia. Using quality of local regulations index constructed by the Indonesia's Regional Autonomy Watch (KPPOD) as measure of institutions, We found that better institutional quality at the local level was associated with more innovation and that firms experiencing major obstacle in access to finance were less likely to innovate. Access to finance is more critical for small and medium enterprises (SMEs) whereas institutional quality is more important for large firms. The positive impact of better institutions on innovation is asymmetrically distributed. Better local institutional quality disproportionately benefited non-constrained firms.